Aplikasi Tes Buta Warna Berbasis Virtual Reality - Subari Subari; Moh Alek Mustofa (J-INTECH ( Journal of Information and Technology), 2021)
Health is the most beautiful gift that given by Allah SWT. Moreover, health is related to the eyes. One disease that is commonly discovered in society is color blindness. Color blindness is a condition where a person's eyes cannot distinguish several colors that can be seen by normal people's eyes. There are several test methods used to detect color blindness, one of them is Ishihara method test. Ishihara method test is a test used to detect color perception disorders. The form is using special table that is a pseudoisochromatic sheet which is composed of dots with different color densities that can be seen using normal eyes, but cannot be seen using eyes with partial color deficiency. By using Ishihara method, the color blindness of person can be identified. Color blindness is divided into two types, total color blindness and partial color blindness. The development of technology in this era cannot be prevented by many emerging technologies, one of them is virtual reality. Virtual reality technology provides a different experience by bringing someone into a virtual world that resembles to the real world. The use of this technology has been widely used, starting from the health aspect, area mapping, building architecture, and many smartphone games that support this technology. With the growing popularity of the use of smartphones in the community, the creation of a virtual reality-based color blind test application is expected to be able to help everyone in need. Another tool is needed to operate this application, is called a virtual reality headset. The application of this test can display 3D objects, so that it will be more interesting when using this application.